Integrating IoT Technologies and Public Health Science: A Comprehensive Review (International Journal of Food and Nutritional Sciences, 2022)
The integration of Internet of Things (IoT) technologies into public health science is a dynamic and transformative endeavor. This comprehensive review explores the multifaceted intersection of IoT and public health, with a focus on empirical evidence, challenges, and future trends. We begin by elucidating the fundamentals of IoT technologies and their application in public health, emphasizing their role in disease surveillance, telemedicine, environmental monitoring, wearable health devices, and medication management. Drawing on empirical studies, we present evidence of IoT's positive impact on public health outcomes, including improved disease prevention, enhanced healthcare access, and better patient outcomes.